Keberkesanan pengeluaran hakmilik kekal berdasarkan pindaan Kanun Tanah Negara 1965 (AKTA A1104) - Ibrahim, Alias (2005)
The issues of delay in the registration of the Final Title began since 1960. Lately, with the application of modern technology in land administration, these issues still a major problem for Land Administrators. Without a Final Title, the landowners have to wait for years before he is able to sub-divide, partition or amalgamate his land. Delay in issuing of Final Title resulted in the lost of revenue to the State Governments by way of quit rents. The Federal Government through its agency, Department of Director of Land and Mines (DLM) has amended the National Land Code 1965 (NLC 1965) with options of issuing Qualified Title or Final Title. In year 2001, on the amendments to the NLC 1965, by which Final Title may be registered and issued without issuing of Qualified Title in cases of sub-division, partition or amalgamation. Previously, before Final Title in registered, a Qualified Title must first be registered. By this amendment, there will be less number of Qualified Titles registered at Land Office in the country. Therefore, more time can be spent by the Land Officers to settle the issue of converting Qualified Title to Final Title. The objective of this study is to look at the effectiveness of the amendments of section 183A and 185A. However, the purpose of these amendments is not intentionally to abolish the Qualified Titles. This thesis will carry out a theoretical and empirical studies to evaluate the effectiveness of the new amendments. Our main respondents are Land Offices’ staff and Licensed Land Surveyors nationwide. The amendments of NLC 1965 can help to solve problems of replacing the Qualified Title to Final Title